The new industrial revolution and industrial upgrading in China: achievements and challenges. Issue 2 (2nd April 2016) - Tourk, Khairy; Marsh, Peter
Abstract: One recent development in the area of manufacturing is the New Industrial Revolution (NIR). This paper examines the contours shaping the NIR, and analyses the challenges facing China in its pursuit to achieve technological parity with advanced nations. China's economic rise is strongly associated with its ascending the technology ladder. The country is now the world's workshop. As the labour-intensive strategy based on cheap labour has run up against its limits, policy makers have devised plans that focus on industrial upgrading, promote indigenous innovations and establish national brands. This way China would avoid the middle-income trap and eventually become an innovative powerhouse.